Effect of culture conditions on the enzymatic activity of Serratia marcescens against Tecia solanivora (Lepidoptera: Gelechiidae) - BOSA-O., CARLOS FELIPE; COTES-P., ALBA MARINA (Revista Colombiana de Entomología, 2004)
The enzymatic activity of Serratia marcescens extracts was evaluated, previously inoculated or not on Tecia solanivora Povolny larvae, and successively grown in culture media supplemented or not with potential virulence inductors (wheat bran and homogenised T. solanivora larvae). The bacteria biomass obtained from these media were used to prepar enzymatic extracts for which the activity of the enzymes N-acetilglucosaminidase, quimoelastase protease PR-1 and ., Beta-esterase were determined. The bacteria were grown up in five successive cultures on these media, and in each culture these activities were also evaluated. We determined that successive growth of the bacteria on culture media supplemented with these potential substrates affected the extract enzymatic activities, increasing with the third successive growing of S. marcescens in the supplemented culture media, these activities being slighty higher when the bacteria grew on media supplemented with homogenised insect larvae.